The Impact of Tax Advantage for the Leverage of Private Funds for the Orassi Hotel - A Standard Study of the Period 2011–2020 - ferahtia, redouane (Journal of Research in Finance and Accounting, 2022)
The aim of this study is to measure the impact of the tax advantage resulting from borrowing costs, as the main reason for the economic institution's use of fiscal raising is to take advantage of tax savings and increase shareholders’ wealth, and in order to determine the impact of the fiscal raising tax advantage on the private funds of the Orassi Hotel Operating Corporation for the period 2011-2020, we conducted a standard study that showed the absence of a long-term balance relationship, so we adopted the VAR self-regression model that achieved the stability requirement, which is economically and standardly acceptable. The most important results of the estimated model indicate a correlation between the tax advantage of fiscal raising and the return on private funds, which confirms that borrowing is a lever for the wealth of shareholders under good control of financial risks and higher economic returns than the cost of borrowing.